Pengaruh Quality Product, Social Network, dan Celebrity Endorsement terhadap Purchase Intention terhadap Kopi Kenangan Megamall Batam - You, Hendry; Husda, Nur Elfi (J-MAS (Jurnal Manajemen dan Sains), 2024)
Increasingly tight business competition requires companies to continue to innovate in their marketing strategies. Kopi Kenangan is one of the many coffee shops that are easy to find, especially in big cities. Therefore, Kopi Kenangan needs to understand the factors that influence purchase intention in order to maintain and increase their market share. This study aims to analyze the influence of social networks, product quality, and celebrity endorsements on purchase intention at Kopi Kenangan Megamall Batam. This study uses a quantitative approach with a survey method. Sampling was carried out using the Slovin formula, resulting in 100 respondents as research samples. The data collection instrument was a questionnaire with a Likert scale designed to measure the variables of social networks, product quality, celebrity endorsements, and purchase intention. The results of this study indicate that social networks do not affect purchase intention, while product quality and celebrity endorsements have a significant effect on purchase intention. Therefore, Kopi Kenangan needs to develop a promotional strategy through social networks and improve product quality to increase customer purchase intention towards Kopi Kenangan.